2007
DOI: 10.1007/s10067-007-0640-z
|View full text |Cite
|
Sign up to set email alerts
|

HLA class 1 associations in Henoch Schonlein purpura: increased and decreased frequencies

Abstract: Henoch Schonlein purpura (HSP) is the most common vasculitis of childhood. Susceptibility to HSP and associated clinical heterogeneity in HSP may be conferred by a number of genetic loci, including the major histocompatibility complex. We aimed to investigate the implications of the human leukocyte antigen (HLA) class 1 alleles in susceptibility to HSP and determine the possible associations with renal, gastrointestinal (GI), and joint manifestations of the disease. 110 children with HSP (66 boys, 44 girls) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
1
32
2
Order By: Relevance
“…It has been reported that HLA A2, A11, and B35 antigens showed an increased risk for a predisposition to HSP and HSP patients with nephrotic proteinuria had higher HLA-DRB1*13 positivity. 22,23 Results of Amoli et al 24 supported the role of HLA B35 in the susceptibility for HSP patient with nephritis. In another study, transforming growth factor-beta (TGF-b) gene C509T polymorphism was associated with HSP.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that HLA A2, A11, and B35 antigens showed an increased risk for a predisposition to HSP and HSP patients with nephrotic proteinuria had higher HLA-DRB1*13 positivity. 22,23 Results of Amoli et al 24 supported the role of HLA B35 in the susceptibility for HSP patient with nephritis. In another study, transforming growth factor-beta (TGF-b) gene C509T polymorphism was associated with HSP.…”
Section: Discussionmentioning
confidence: 91%
“…HLA-DRB1*01 allele is in linkage disequilibrium with HLA-B35, HLA-B14 and HLA-B27 in Caucasian populations. In particular, the HLA-B35 haplotype was previously described as related to an increased predisposition to HSP (Peru et al, 2008), to HSP recurrent forms (Nathwani et al, 1992) and HSP nephritis. All these clinical features were also associated with HLA-B35 in patient 1.…”
Section: Discussionmentioning
confidence: 99%
“…We studied the correlation of HLA-A and -B polymorphisms in Mongolian and Han children with HSP and found that the susceptible loci of Mongolian patients were HLA-A*11 and HLA-B*15; HLA-A*11 was also reported to be associated with HSP (Peru et al, 2008). The protecting genes were HLA-B*07 and HLA-B*40, and HLA-B*40 was also the protecting gene for hemorrhagic fever in nephrotic syndrome (Luo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%